165k views
0 votes
-2(11-12x)= -4(1-6x)

User Mr Rubix
by
4.2k points

1 Answer

5 votes

The given equation -2(11 - 12x) = -4(1 - 6x) has infinite solutions

Solution:

Given that we have to solve the given expression

Given expression is:

-2(11 - 12x) = -4(1- 6x)

We have to use distributive property to solve the given expression

The distributive property lets you multiply a sum by multiplying each addend separately and then add the products.

Which means,

a(b + c) = ab + ac

Apply this in given expression

-2(11 - 12x) = -4(1-6x)

-22 + 24x = -4 + 24x

When both sides of the equation are simplified, the coefficients are the same, then infinite number of solutions occur

If we end up with the same term on both sides of the equal sign, such as 24x = 24x, then we have infinite solutions

User Noor H
by
4.6k points